Correlation between Duration of Placement of Non-tunneled Hemodialysis Catheter and Positive Bacterial Culture Incidence in Hemodialysis Patients - Djajakusumah, Teguh Marfen; Hapsari, Putie; Yarman, Indra Prasetya; Utomo, Hafidh Seno Radi; Lukman, Kiki; Sulastri, Dian; Ulurrosyad, Muhammad Faiz (Majalah Kedokteran Bandung, 2024)
Non-tunneling hemodialysis catheter is one of the most convenient vascular accesses for hemodialysis in End Stage Kidney Disease (ESRD) patients. However, these catheters have the highest morbidity among all available accesses. Current guidelines recommend that non-tunneled hemodialysis catheters be placed for no more than 2 weeks to prevent bacterial contamination. This study was conducted in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, throughout January-December 2021. A correlation test with a prospective observational analysis design was applied to find the link between the duration of non-tunneled hemodialysis catheter placement and the incidence of positive bacterial culture on the catheter. Pearson correlation test was used to see the strength of the correlation, with a significance limit of 0.05. This study involved 28 subjects. The most common location for catheter placement was in the jugular vein, and laboratory examinations showed no correlation between leukocyte values and positive bacterial culture results. Hypertension and diabetes mellitus were not significant risk factors (p-value 0.887). At ≤14 days of catheter placement, only 1 (6.7%) of the subjects presented a positive culture result. Most of the positive bacterial culture results were found at a duration of 15-30 days of placement, (n=8; 53.3%). The results of the Pearson test showed a p-value of 0.036 and an r-value of 0.399, indicating a significant result with a strong correlation between the two variables. The duration of placement of hemodialysis catheters has a positive correlation with the incidence of positive bacterial cultures, which can increase the risk of systemic infection associated with hemodialysis catheters.